Penurunan progesterone-induced blocking factor (PIBF) sebagai penanda preeklampsia - Achmad Salman; Budi Wicaksono; Erry Gumilar Dachlan; Widjiati Widjiati (Universitas Airlangga, 2016)
Background: Pathogenesis of preeclampsia still a controversial research objects. Progesterone induced blocking factor has protective effects in pregnancy.Objectives: To compare PIBF serum level and placental weight and investigate correlation between both in preeclampsia.Methods: This experimental study used 16 Mus musculus with normal pregnancy and 16 Mus musculus that were injected with anti Qa-2 to create a preeclampsia model. Terminations of were performed in day 16th, followed by ELISA examination for PIBF serum level and placental weight measurement.Result: PIBF serum level significantly reduced on preeclampsia model compared with control (33,21±29,36 ng/ml vs 105,76±59,69 ng/ml; p<0,05). There was no different of placental weight in preeclampsia model compared with control (97,75±50,74 mg vs 116,09±44,45 mg; p>0,05). There was no significant correlation between PIBF serum level and placental weight.Conclusion: Decreased of PIBF serum level could be used as a marker of preeclampsia. Decreased of PIBF serum level may be correlate with placental pathology in preeclampsia.